PENGARUH PERSEPSI KUALITAS PELAYANAN TERHADAP NIAT MEMBELI ULANG YANG DIMEDIASI OLEH KEPERCAYAAN PADA TENAGA PENJUAL DI TOKO RITEL LYRADYBA KOTA BANDA ACEH - Diba Nurfath, Sorayanti Utami (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This research aims to know the influence of perceived service quality towards repurchase intention with trust of salesperson as the mediating variable. The sample used in this study were 100 people which are the customer of Lyradyba retail store in Banda Aceh. Purposive sampling is used as the sampling technique. The analysis method is Hierarchichal Linear Modelling (HLM) is used as the method of analysis to find out the influence of  the variables involved. The results of this research indicates that perceived service quality significantly affect the repurchase intention. In addition to obtain with the result, the trust of salesperson variable partially mediates the influence of perceived service quality towards the repurchase intention. It also suggests that the better the perceived quality given, the higher the trust of the salesperson, and the stronger the repurchase intention of the customer.   Keyword: Perceived Service Quality, Repurchase Intention, Trust of   Salesperson, Retailing